Benchmarking Social Spending Using Efficiency Frontiers - Kapsoli, Javier (IMF Working Papers; Working Paper ;, 2017)
Developing and low-income economies face the challenge of increasing public spending to address sizeable infrastructure and social gaps while simultaneously restoring the fiscal discipline weakened to countervail the effect of the global recession. Increasing the efficiency of social spending could be the key policy to address the dilemma as it allows the optimization of the existing resources by reducing spending inefficiencies. This paper quantifies the efficiency gap in the health and education sectors for a large sample of developing and emerging countries and proposes measures to reduce these gaps for the specific cases of El Salvador, Guatemala, and Honduras.